Effect of Fermentation Time and Lactobacillus plantarum Inoculum Concentration on Lactic Acid Production from Durian Peel Waste - Nanda Yunita Pratiwi; Shintya Hotnauli Turnip; Sani Sani; Raka Selaksa Charisma Muchammad; Aisyah Alifatul Zahidah Rohmah; Suprihatin Suprihatin (Universitas Islam Raden Rahmat, Malang, 2026)
Lactic acid is an important chemical whose demand continues to increase every year. Therefore, alternative innovations are needed to meet this demand. One potential raw material that can be utilized is durian peel waste, which is high in cellulose and can be converted into reducing sugar through pretreatment and hydrolysis as a fermentation substrate to produce lactic acid. This study aims to determine the optimal conditions for fermentation time (5 hours; 6.5 hours; 8 hours; 9.5 hours and 11 hours) and Lactobacillus Plantarum inoculum concentration (5%, 10%, 15%, 20%, 25%) in producing high concentrations of lactic acid. The research was conducted through Alkali Hydrogen Peroxide (AHP) delignification, acid hydrolysis, and fermentation processes. The lactic acid content was analyzed using the acid-base titration method (Total Titratable Acidity). The results showed that the highest lactic acid content was obtained at a fermentation time of 11 hours with an inoculum concentration of 20%, which reached 0.135%. Thus, fermentation time and inoculum concentration affect the lactic acid content produced, and durian peel waste has the potential to be used as an alternative raw material in lactic acid production.